Enantioselectivity of Chiral Derivatives of Xanthones in Virulence Effects of Resistant Bacteria - Fernando Durães; Sara Cravo; Joana Freitas-Silva; Nikoletta Szemerédi; Paulo Martins-; Eugénia Pinto; Maria Elizabeth Tiritan; Gabriella Spengler; Carla Fernandes; Emília Sousa; Madalena Pinto (MDPI AG, 2021)
Antimicrobial peptides are one of the lines of defense produced by several hosts in response to bacterial infections. Inspired by them and recent discoveries of xanthones as bacterial efflux pump inhibitors, chiral amides with a xanthone scaffold were planned to be potential antimicrobial adjuvants. The chiral derivatives of xanthones were obtained by peptide coupling reactions between suitable xanthones with enantiomerically pure building blocks, yielding derivatives with high enantiomeric purity. Among 18 compounds investigated for their antimicrobial activity against reference strains of bacteria and fungi, antibacterial activity for the tested strains was not found. Selected compounds were also evaluated for their potential to inhibit bacterial efflux pumps. Compound (R,R)-8 inhibited efflux pumps in the Gram-positive model tested and three compounds, (S,S)-8, (R)-17 and (R,S)-18, displayed the same activity in the Gram-negative strain used. Studies were performed on the inhibition of biofilm formation and quorum-sensing, to which the enantiomeric pair 8 displayed activity for the latter. To gain a better understanding of how the active compounds bind to the efflux pumps, docking studies were performed. Hit compounds were proposed for each activity, and it was shown that enantioselectivity was noticeable and must be considered, as enantiomers displayed differences in activity.